2021
DOI: 10.3390/jcm10163602
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Shockwave Therapy (ESWT) Alleviates Pain, Enhances Erectile Function and Improves Quality of Life in Patients with Chronic Prostatitis/Chronic Pelvic Pain Syndrome

Abstract: Purpose: Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS), affecting over 90% of patients with symptomatic prostatitis, remains a therapeutic challenge and adversely affects patients’ quality of life (QoL). This study probed for likely beneficial effects of ESWT, evaluating its extent and durability. Patients and methods: Standardized indices, namely the pain, urinary, and QoL domains and total score of NIH-CPSI, IIEF-5, EHS, IPSS, and AUA QoL_US were employed in this study of patients with CP/CPPS w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
1
9
1
2
Order By: Relevance
“…Wu's paper shows that a pre-ESWT IPSS of 13.9 recorded a 27.1%, 38.0%, 42.0%, and 50.9% time-dependent improvement up to 1 year of result collection. 20 This was also concordant with Zimmerman's findings, which reported a 25% decrease in IPSS 3 months after ESWT. 7 Our study also demonstrated significant improvements in the frequency, urgency, weak stream, straining, and total score domain of the IPSS.…”
Section: Discussionsupporting
confidence: 88%
“…Wu's paper shows that a pre-ESWT IPSS of 13.9 recorded a 27.1%, 38.0%, 42.0%, and 50.9% time-dependent improvement up to 1 year of result collection. 20 This was also concordant with Zimmerman's findings, which reported a 25% decrease in IPSS 3 months after ESWT. 7 Our study also demonstrated significant improvements in the frequency, urgency, weak stream, straining, and total score domain of the IPSS.…”
Section: Discussionsupporting
confidence: 88%
“…In 3 months after treatment in patients with maximum urinary ow rate increases, the bladder residual urine volume decreases. In the CPPS study (72), the experimental group treated with perineal ESWT (3000 pulses, 0.25 mJ/mm 2 , 4Hz) weekly experienced a reduction in refractory pain and a signi cant improvement in quality of life after 6 weeks of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Wu и соавт. (2021)[21] c целью оценки долгосрочного влияния ЭУВТ провели когортное проспективное исследование с участием 215 мужчин с ХП/СХТБ категории IIIВ, рефрактерных к медикаментозной терапии. Всем исследуемым выполнено ЭУВТ по протоколу, включающему 3000 ударов с энергией 0,25 мДж/мм 2 и частотой 4 Гц 1 раз в неделю в течение 6 нед с использованием аппарата DUOLITH ® SD1 (Storz Medical AG, Швейцария).…”
unclassified
“…Оценивались общий балл по NIH-CPSI, IPSS, МИЭФ-5, качество жизни при урологических симптомах согласно Американской урологической ассоциации (AUA QOL_US), шкала твердости эрекции (Erection Hardness Score, EHS) до и сразу после курса терапии, а также через 1, 2, 6 и 12 мес после лечения. Результаты исследования продемонстрировали, что ЭУВТ статистически значимо улучшает качество жизни, облегчает боль, улучшает эректильную функцию и окончательный эффект проявляется через 12 мес после курса терапии[21].Е.В. Кульчавеня и соавт.…”
unclassified